2012
DOI: 10.1534/genetics.111.136721
|View full text |Cite
|
Sign up to set email alerts
|

Scrambling Eggs: Meiotic Drive and the Evolution of Female Recombination Rates

Abstract: Theories to explain the prevalence of sex and recombination have long been a central theme of evolutionary biology. Yet despite decades of attention dedicated to the evolution of sex and recombination, the widespread pattern of sex differences in the recombination rate is not well understood and has received relatively little theoretical attention. Here, we argue that female meiotic drivers-alleles that increase in frequency by exploiting the asymmetric cell division of oogenesis-present a potent selective pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
127
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(139 citation statements)
references
References 97 publications
9
127
3
Order By: Relevance
“…In sharp contrast with the situation in plants, only eight of the 164 species considered in the last review on heterochiasmy [8] are hermaphroditic animals, and we found just a few additional cases in the literature (table 1). In these studies, heterochiasmy estimates are derived from chiasma counts (i.e.…”
Section: Introductioncontrasting
confidence: 70%
See 2 more Smart Citations
“…In sharp contrast with the situation in plants, only eight of the 164 species considered in the last review on heterochiasmy [8] are hermaphroditic animals, and we found just a few additional cases in the literature (table 1). In these studies, heterochiasmy estimates are derived from chiasma counts (i.e.…”
Section: Introductioncontrasting
confidence: 70%
“…that the centromeres are located close to the chromosome periphery. Among the different hypotheses put forward to explain heterochiasmy [6][7][8][9][10][11][12][13][14], meiotic drive stands out by precisely predicting heterogeneous patterns of heterochiasmy along chromosomes and stronger heterochiasmy close to the centromeres [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their relevance to an understanding of gene clusters, our results might also contribute to an enhanced understanding of the evolution of sex-specific recombination rates [26,27]. Previous models to explain sex-specific recombination rates require certain of the properties of our model and results, namely haploid (or pseudo-haploid) selection pressure and sex-specific LD.…”
Section: Discussionmentioning
confidence: 86%
“…It should also be noted that the linkage-disequilibrium method can yield only estimates for historical populationlevel and sex-averaged crossover rates. Thus, this method is not suitable for examining the variation of recombination rate between individuals and sexes (e.g., Coop and Przeworski 2007;Kong et al 2010;Brandvain and Coop 2012;Comeron et al 2012;Bauer et al 2013). Furthermore, it is well known that crossover, the reciprocal exchange of DNA between homologous chromosomes, only represents a small proportion (often ,20%) of the total recombination events, with the rest generating nonreciprocal, gene-conversion events (Langley et al 2000;Malkova et al 2004;Morrell et al 2006;Mancera et al 2008;Yang et al 2012;Lynch et al 2014).…”
mentioning
confidence: 99%